CREATION OF MARK BOESLAV IN CONTEXT OF LITERATURE OF UKRAINIAN RESISTANCE (TO 100-ANNIVERSARY FROM THE DAY OF BIRTH) - Zelinsca, G. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Creation of Mark Boeslav (Mihaylo Dyachenco) – poet-warrior UPA on a background the aesthetically ideological-beautiful searches of writers of Ukrainian literature of resistance is examined in the article (resistance).